Hybrid 3D/2D Complete Inception Module and Convolutional Neural Network for Hyperspectral Remote Sensing Image Classification - Firat, Huseyin; Asker, Mehmet Emin; Bayindir, Mehmet Ilyas; Hanbay, Davut (Springer, 2023)
Classification in hyperspectral remote sensing images (HRSIs) is a challenging process in image analysis and one of the most popular topics. In recent years, many methods have been proposed to solve the HRSIs classification problem. Compared to traditional machine learning methods, deep learning, especially convolutional neural networks (CNNs), is commonly used in the classification of HRSIs. Deep learning-based methods based on CNNs show remarkable performance in HRSIs classification and greatly support the development of classification technology. In this study, a method in which the Hybrid 3D/2D Complete Inception module and the Hybrid 3D/2D CNN method are used together has been proposed to solve the HRSIs classification problem. In the proposed method, multi-level feature extraction is performed by using multiple convolution layers with the Inception module. This improves the performance of the network. Conventional CNN-based methods use 2D CNN for feature extraction. However, only spatial features are extracted with 2D CNN. 3D CNN is used to extract spatial-spectral features. However, 3D CNN is computationally complex. Therefore, in the proposed method, a hybrid approach is used by first using 3D CNN and then 2D CNN. This reduces computational complexity and extracts more spatial features. In addition, PCA is used as a preprocessing step for optimum spectral band extraction in the proposed method. The proposed method has been tested using Indian pines, Salinas, University of Pavia, HyRANK-Loukia and Houston datasets, which are frequently used in studies for HRSIs classification. The overall accuracy of the proposed method in these five datasets are 99.83%, 100%, 100%, 90.47% and 98.93%, respectively. These results reveal that the proposed method provides higher classification performance compared to state-of-the-art methods.
Keywords: Remote sensing; Hyperspectral image classification; Inception model; Convolutional neural network